Survey of extended-spectrum beta-lactamases in Escherichia coli isolates from a Portuguese hospital and characterisation of a novel class 1 integron (In60A) carrying the bla(CTX-M-9) gene - Brizio, Ana (2015)
Between November 2001 and November 2004, 231 Escherichia coli isolates resistant to P-lactam antibiotics were identified. In 14 isolates, bla(TEM-24) (2 isolates), bla(TEM-52) (5 isolates) and bla(TEM-26) (7 isolates) were identified. In 145 E. coli isolates with the same M13 fingerprinting profile and the same resistance phenotype, the bla(CTX-M-15) gene was found in association with an insertion sequence ISEcp1. The bla(CTX-M-2) gene was identified in one E. coli isolate (290HSM), and in other E. coli isolate (246HSM) the bla(CTX-M-9) gene was contained in a new complex sull-type class 1 integron (named In60A). This is the first report of three cefotaximases (CTX-M-15, CTX-M-2 and CTX-M-9) in E. coli isolates from a Portuguese hospital. (c) 2006 Elsevier B.V. and the International Society of Chemotherapy. All rights reserved.